2015
DOI: 10.1128/mcb.00029-15
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Mediated Reversible Silencing of Sense-Antisense Gene Pairs in Embryonic Stem Cells Is Consolidated upon Differentiation

Abstract: Genome-wide gene expression studies have indicated that the eukaryotic genome contains many gene pairs showing overlapping sense and antisense transcription. Regulation of these coding and/or noncoding gene pairs involves intricate regulatory mechanisms. In the present study, we utilized an enhanced green fluorescent protein (EGFP)-tagged reporter plasmid cis linked to a doxycycline-inducible antisense promoter, generating antisense transcription that fully overlaps EGFP, to study the mechanism and dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The formation of triplexes can generate CpG methylation, as shown for PARTICLE and MAT2A SAGP in cells exposed to radiation 20 . Recent data also strongly support a role of antisense transcription of SAGP in the generation of H3K36me3 marks, in the developmental mechanisms of yeast, and in the Igf2r promoter of mouse embryonic stem cells (ESC) 21 . The H3K36me3 mark could play a major role in the de novo methylation of the CpG island.…”
Section: Discussionmentioning
confidence: 82%
“…The formation of triplexes can generate CpG methylation, as shown for PARTICLE and MAT2A SAGP in cells exposed to radiation 20 . Recent data also strongly support a role of antisense transcription of SAGP in the generation of H3K36me3 marks, in the developmental mechanisms of yeast, and in the Igf2r promoter of mouse embryonic stem cells (ESC) 21 . The H3K36me3 mark could play a major role in the de novo methylation of the CpG island.…”
Section: Discussionmentioning
confidence: 82%
“…The antisense-mediated repression may involve transcriptional perturbation of the sense partner but may also include engagement of chromatin remodeling complexes, with local accumulation of histone modifications and DNA methylation. Alternatively, chromatin modulation based on the process of transcription per se might be involved ( 73 ). This model is supported by the association of Pol II with chromatin remodelers like Set2, which catalyzes the deposition of H3K36me3 in transcribed regions ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…But a recent report exhibited that transcriptional interference of the sense gene of a sense-antisense convergent gene reporter was coupled with H3K36me3, which was enriched by the antisense promoter activation. 27 The maintain system of this transcriptional interference of the sense gene changes depending on the state of the cell. H3K36me3 is promptly removed by the inactivation of the antisense promoter in ES cells, but it is maintained even after the inactivation of the antisense promoter to repress the transcription from the sense strand as a transcriptional memory in differentiating cells.…”
Section: Set2-dependent H3k36mementioning
confidence: 99%
“…H3K36me3 is promptly removed by the inactivation of the antisense promoter in ES cells, but it is maintained even after the inactivation of the antisense promoter to repress the transcription from the sense strand as a transcriptional memory in differentiating cells. 27 In fission yeast, Set2 is the sole methyltransferase that produces all methylation states of H3K36. We found that in set2DSRI cells, H3K36me3 was abolished while H3K36me2 was unaffected.…”
Section: Set2-dependent H3k36mementioning
confidence: 99%